Manifestations of Internalized Patriarchal Norms in Taylor Jenkins Reid’s The Seven Husbands of Evelyn Hugo (2017): Feminist Perspective - Chairunnisa, Ainul; Al Hafiz, Muhd (English Language and Literature, 2024)
Male domination manifests patriarchal practices that navigate societal expectations on women. Through patriarchal societal norms, women become socialized into patriarchal structure. Because of the oppression and discrimination that has been maintained by patriarchal norms, it causes women to have internalized patriarchal norms. In the novel The Seven Husbands of Evelyn Hugo (2017) by Taylor Jenkins Reid, the issue of compulsory heterosexuality, male domination and internalized patriarchal norms are being explored. This research used qualitative approach, focusing on the interpretation of human experiences and perspective by using feminist literary criticism. The analysis uses patriarchy and feminist theory by Catharine A. Mackinnon, Julia Kristeva and Sylvia Walby, and compulsory heterosexuality theory by Adrianne Rich and Judith Butler. This research found four forms of internalized patriarchal norms. The internalized of patriarchal norms causes women being the subject of domestic, power and law abuse, and discriminations from patriarchal society. By using “Four Faces of Resistance” by Eric S. Knowles and Jay A. Linn, Abjection and Semiotic by Julia Kristeva, Subversion of Norms by Judith Butler and Lesbian Continuum by Adrianne Rich, this research also finds five form of resistance. Women demonstrate the resistance to challenge how patriarchal norms are manifested through internalized patriarchal norms.